Genome analysis of methicillin resistance in Macrococcus caseolyticus from dairy cattle in England and Wales. Issue 8 (19th June 2018) - MacFadyen, Alison C.; Fisher, Elizabeth A.; Costa, Ben; Cullen, Cassie; Paterson, Gavin K.
Abstract : Species of the genus Macrococcus are widespread commensals of animals but are becoming increasingly recognised as veterinary pathogens. They can encode methicillin resistance and are implicated in its spread to the closely-related, but more pathogenic, staphylococci. In this study we have identified 33 isolates of methicillin-resistant Macrococcus caseolyticus from bovine bulk tank milk from England and Wales. These isolates were characterised to provide insight into the molecular epidemiology of M. caseolyticus and to discern the genetic basis for their methicillin resistance. Antimicrobial susceptibility testing was performed by Vitek2 and disc diffusion. Isolates were whole-genome sequenced to evaluate phylogenetic relationships and the presence of methicillin resistance determinants, mecA – D . All 33 isolates were phenotypically methicillin-resistant according to cefoxitin disc diffusion, cefoxitin Etest and oxacillin resistance assessed by Vitek2. In contrast only a single isolate was resistant in the Vitek2 cefoxitin screen. Twenty-seven isolates were positive for mecD and six were positive for mecB. mecA and mecC were not detected. The results of phylogenetic analysis indicated that these methicillin-resistant isolates represented a heterogeneous population with both mecB and mecD found in diverse isolates. Isolates had a widespread distribution across the sampled region. Taken together with the role of M. caseolyticus in veterinary infections, including bovine mastitis, and in the potential spread of methicillin resistance to more pathogenic staphylococci, this work highlights the need to better understand their epidemiology and for increased awareness among veterinary microbiology laboratories.